(untitled) (Modern education and development, 2025)
Grammar instruction has long been seen as crucial to language proficiency development. As a result, this article offers a five-step grammar instruction strategy. This approach, which I developed, blends the ideas of practice and consciousness-raising with explicit and implicit knowledge, as well as deductive and inductive grammar teaching methods. My experience as a grammar teacher and my strong interest in creative grammar instruction led to the development of this approach. It is expected that the proposed measures will give English teachers another way to teach grammar, especially when it comes to teaching tenses and modals in college and university settings or even in elementary schools.